Effects of polymer and surfactant complex with microbubble on the flow enhancement of liquids in pipelines - Oluwasoga, Akindoyo Edward (2016)
The major challenges confronting pipeline transportation of fluids are cost of transportation and energy dissipation. Such challenges are caused by the fluid turbulent flow. There are several attempted approaches to reduce the cost as well as the energy dissipated which have initially proven abortive. The main reason for this been that, there is no universal approach to reduce such turbulence as well as cost of liquid transportation. This turbulence flow, which leads to drag in the pipeline, has initially been attempted to reduce with active, passive and interactive means. However, safest practices, environmental consideration and less cost have prompted a continuous research in this area. Microbubbles, due to the environmental friendly nature and economic feasibility have as well been investigated by several researchers. However, the problem of coalescence is a major drawback to its general acceptance. This present work presents an approach to investigate and evaluate the effects of polymers, surfactant alone, complexes formed from these additives, each of these additives and their complexes with microbubbles. Such is aimed at changing the flow behavior in the pipeline. In this present work, Xanthan gum (XG), Polyacryl amide (PAM), Polyethylene Oxide (PEO), Hexadecyltrimethyl ammonium chloride (HTAC), Sodium dodecyl sulfate (SDS) were used as drag reducing agents (DRAs). These were tested in the Rotating Disk Apparatus (RDA) and also in the pipe. Rotating Disk apparatus was conducted to simulate external flows as well as mimic the high turbulence in the pipe. The pipeline loop was used to individually study the materials, their complexes as well as the combination of either of these with microbubbles. Materials were prepared in 50, 100, 200, 500, 700 and 1 OOOppm as the concentration and data were taken for their pressure drop across the sections of the pipe at varying flow rates. Such were used to evaluate drag reduction capability of these DRAs. From the result, it was observed that concentration played important roles in each of the materials investigated both in the RDA and pipeline. For the RDA, the best performance was obtained for Xanthan gum at 700ppm and a total drag reduction of about 53% was recorded while 47% and 43% for PAM and PEO at lOOOppm respectively. For the HTAC and the SDS, only 39 and 32 percent were recorded for each at lOOOppm. In the pipe, best performances were observed with the three dimensional complexes with microbubbles. Microbubbles alone gave 12% drag reduction, while microbubbles with three dimensional complex of XG 700ppm-HTAC lOOOppm-SP has the best drag reduction performance overall of about 87% drag reduction. Other complexes with microbubbles, such as XG 700ppm-SDS lOOOppm-SP, PAM lOOOppm-HTAC lOOOppmSP, PEO lOOOppm-HTAC lOOOppm-SP, PAM lOOOppm-SDS lOOOppm-SP, PEO lOOOppm-SDS lOOOppm-SP only approximately 79%, 77%, 72%, 64% and 57% drag reduction respectively. However, when these complexes were investigated without microbubbles, they performed less as the following results were obtained: XG 700ppmHTAC lOOOppm-SP, XG 700ppm-SDS lOOOppm-SP, PAM lOOOppm-HTAC lOOOppmSP, PEO lOOOppm-HTAC lOOOppm-SP, PAM lOOOppm-SDS lOOOppm-SP, PEO lOOOppm-SDS lOOOppm-SP with 73, 62, 59, 58, 54, 51 drag reduction percentage respectively. From the observation for the pipe, it could be suggested that, the microbubbles played important role on the complexes compared to those obtained from without micro bubbles or the RDA.